Kombinasi Algoritma Sandi Caesar dan Algoritma RSA untuk Pengamanan Pesan Teks - Alamsyah, Alifa Raida; Kurniadi, Edi; Triska, Anita; Sylviani, Sisilia (Mathematical Sciences and Applications Journal, 2024)
This article combines a simple cryptographic algorithm, Caesar Cipher, with a more complex algorithm, RSA, in order to increase the security of encrypted text messages. Text messages are first encrypted with the Caesar Cipher algorithm, which is then re-encrypted using the RSA algorithm. By utilizing number theory, specifically about integers and modulo arithmetic in the RSA algorithm, a public key and a secret key are obtained that will increase the security of the encryption process in this article. Due to the increased security of the text message, uninvolved parties cannot read the actual text message.